2016
DOI: 10.4068/cmj.2016.52.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Altered Nitric Oxide System in Cardiovascular and Renal Diseases

Abstract: Nitric oxide (NO) is synthesized by a family of NO synthases (NOS), including neuronal, inducible, and endothelial NOS (n/i/eNOS). NO-mediated effects can be beneficial or harmful depending on the specific risk factors affecting the disease. In hypertension, the vascular relaxation response to acetylcholine is blunted, and that to direct NO donors is maintained. A reduction in the activity of eNOS is mainly responsible for the elevation of blood pressure, and an abnormal expression of iNOS is likely to be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 94 publications
2
79
0
9
Order By: Relevance
“…reported that neuronal NOS protein expression remained unchanged after adaptation to hypoxia. [2829] Our finding demonstrated that oxidative stress induced by X-ray radiation depended on the dose of X-ray radiation. High-dose X-ray radiation-induced severe oxidative stress resulted from high NO concentration catalyzed by eNOS and iNOS.…”
Section: Discussionmentioning
confidence: 70%
“…reported that neuronal NOS protein expression remained unchanged after adaptation to hypoxia. [2829] Our finding demonstrated that oxidative stress induced by X-ray radiation depended on the dose of X-ray radiation. High-dose X-ray radiation-induced severe oxidative stress resulted from high NO concentration catalyzed by eNOS and iNOS.…”
Section: Discussionmentioning
confidence: 70%
“…The excessive NO production may exert detrimental effects under disease. 13 In the liver brosis patients, a relative correlation was observed between iNOS and TGF-b1. Samples with low brosis displayed a faint positivity for iNOS and less TGF-b1 positive cells, while the expression of both proteins was increased in those with advanced brosis.…”
Section: 10mentioning
confidence: 99%
“…This change was consistent with other previous studies. 13,[26][27][28] The morphologic changes were accompanied by the increases in the expression of a-SMA, collagen, and bronectin. To conrm the anti-brotic effect of SKLB023, we investigated the effect of SKLB023 on tubular interstitial brotic score, ECM deposition, collagen expression and broblast activation in UUO models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma nitrate/nitrite, a marker of total body NO synthesis, are reduced in rats and mice made hypertensive by dexamethasone treatment. The reduced availability of NO might result from a range of influences on the NO biosynthetic pathways: i) alteration in the activity and expression of NO synthases ii) decreased availability of tetrahydrobiopterin (BH4), a NOS cofactor, iii) decreased NO precursor L-arginine and iv) increased NO removal via its interaction with superoxide to form peroxynitrite 14 . Ingestion of dietary nitrate (beetroot juice) results in increased plasma nitrite concentration via bioconversion in vivo.…”
Section: Figure 8: Tracing Of Mibp Record Of Control Group ©Pharmacementioning
confidence: 99%